Analysis of Visual Communication as a Means of Facing the Challenges of Technological Development in a Securities Company - Wijaya, William Surya; Putranto, Algooth (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This illustrates that all countries have the same goals in seeking growth, development, progress, and continuous learning to face challenges in the future. The visual emails presented in this study aim to expand the understanding of the denotative, connotative, and mythical meanings believed to be true through the application of the value expectation theory. This theory provides a comprehensive approach to understanding how individuals form and interpret the meaning of a concept or idea, considering the aspect of value expectation. In this research, Roland Barthes' semiotics method is employed for analyzing main interpretations and representations to unravel the denotative, connotative, and mythical meanings in the presented visuals. Data collection techniques involve focus group discussions and structured in-depth interviews aligned with investor feedback. Based on the research results, exploration will be conducted on how individual perceptions of value influence their interpretation of visual understanding. This is supported by the expectation from feedback that investors desire visuals and text to support technical knowledge and portfolio growth based on the visual analysis provided by the securities company.